Delayed marriage, contraceptive use, and breastfeeding: Fertility patterns over time and wealth quintiles in sub-Saharan Africa - Jocelyn E. Finlay; Iván Mejía-Guevara; Yoko Akachi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The rate of fertility decline has been slow in sub-Saharan Africa (SSA). Using the Demographic and Health Surveys for 21 SSA countries between 1990 and 2014, we examine the within-country fertility patterns by wealth, applying the Bongaarts (2015) proximate determinants model. We find that overall, fertility has declined in SSA for the richest, but not for the poorest, and this translates to a slow decline in the national-level total fertility rate. We find that breastfeeding periods are generally declining, putting upward pressure on the fertility rate. Contraceptive use is increasing, particularly for the richest, reducing fertility for these quintiles alone.
Keywords: J11; J13; 330; proximate determinants of fertility; contraceptive use; delay of marriage; breastfeeding; demographic dividend; sub-Saharan Africa